Connecting community service to careers in public service - Peele, Lydia (My University, 2015)
This paper summarizes research done in conjunction with my summer fellowship with the Government Affairs Team at the Partnership for Public Service in Washington, D.C. I particpated in a conference call on July 21 with the "United We Serve" public affairs team (sponsored by the Corporation for National and Community Service), who connected me with surveys and research conducted by AmeriCorps. From this research, I learned that not only is community service on the rise despite current economic challenges, but participation in organized community service has a direct link to a career in public service.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Peele, L. (2009). Connecting community service to careers in public service. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: AmeriCorps (U.S.); Voluntarism--United States; Civil service--United States; Reports; Reports